Influence of Teamwork, Occupational Safety and Health, and Work Discipline on Employee Performance at the Ungaran Post Office - Yulfa, Laila Indana; Violinda, Qristin; Utami, Ratih Hesty (Journal of Business Management and Economic Development, 2024)
This research aims to determine the influence of Teamwork, Occupational Safety and Health, and Work Discipline on Employee Performance at the Ungaran Post Office. This research uses quantitative research methods. The population used in the research is all employees who work at the Ungaran Post Office in 2023. The sample used in this research is Saturated Sampling which is included in Non Probability Sampling, which means that all members of the population are sampled, namely 80 employees. Analysis of research data using SPSS for Windows software version 24. The results of this research show that there is a positive and significant influence between Teamwork (X1) on Employee Performance (Y), partially with this t count of 7.090 and a significance value of 0.000 with an increase in Teamwork can be achieved. Affects the Employee Performance variable by 23.2%. Occupational Safety and Health (X2) has a positive and significant effect on Employee Performance (Y), partially t count is 21.042 and a significance value of 0.000 with an increase in Occupational Safety and Health can influence the Employee Performance variable by 77.5%. Work Discipline (X3) has a positive and significant effect on Employee Performance (Y), partially the t count is 3.939, a significance value of 0.000 with an increase in Work Discipline can influence the Employee Performance variable by 26.5%. The results of the Coefficient of Determination (R2) test obtained an Adjusted R Square value of 0.850 or 85.0%, indicating that the Employee Performance variable is influenced by Teamwork, Occupational Safety and Health, and Work Discipline while the remaining 0.15 or 15% is influenced by other variables that are not in this study.